Character Values of Tenth-Grade Students during Learning Physics in Vector Material - Astalini; Darmaji; Kurniawan, Dwi Agus; Qoidah, Nikma Nur; Zannah, Miftahul; Triani, Elza (Jurnal Pendidikan Indonesia, 2023)
The formulation of the research problem is that the lack of character education for students can cause a moral crisis which results in negative behaviour in society. The research objective was to analyze the character values ​​of class X students in learning vector material physics. This type of research is a qualitative method in the form of a document study. The subject of the study was the book of a high school physics teacher in class X 2013 curriculum on vector material. The research data collection technique is a literature study by analyzing the teacher's book. The results showed that the character values ​​of class X students in learning vector material physics can shape the students' self-character so that they become moral, noble, tolerant, tough, and well-behaved individuals. So, it can be said that the character values ​​that the teacher instils in students still have a number of characters that are not contained in class X vector material so that there are negative short-term and long-term impacts on students. In conclusion, the teacher has an important role in instilling character values ​​in students through learning vector material physics. There are several character values ​​that are not stated, in the future the researchers hope that educators will apply the 18-character values ​​in vector material physics learning to make it more effective.